Perspectives on Commercial Law Enforcement in the Era of Digitalization and Globalization - Taufik Hidayat Batubara; Adelia Salsabila Marbun; Aqtika Deeba Lubis; Muhammad Agis Nirodi (ISNU Sumatera Utara, 2025)
One of the most significant forces behind this change is digitalization. While facilitating a wide range of direct information and commercial transactions through digital platforms, these procedures also pose new challenges for the rules and laws governing the operations of global companies. In addition to discussing the difficulties and tactics involved in developing a current and flexible legal framework, this essay also examines how globalization and digitalization have impacted commercial law. Its primary focus is on how commercial law can foster inclusive economic growth, address the digitalization of trade, and resolve regulatory disparities. Trade law must be able to lower trade barriers in the context of globalization that prevent poor countries from accessing international markets. Case studies and a literature review are among the research techniques used. While case studies offer a practical dimension by examining actual examples of the application of commercial law in the context of globalization and digitalization, the literature review seeks to explore sources of information that discuss changes in commercial law with the advent of globalization and digitalization. The study's conclusion highlights the importance of cross-sector engagement and successful tactics in creating an appropriate legal framework considering the evolving realities of international trade in the digital age. As a result, this essay provides a comprehensive understanding of the regulatory nuances surrounding international trade alongside legal remedies and appropriate approaches to address the difficulties that arise in the digital age.